Application of deterministic model of isothermals for population dynamics of Synthesiomyia nudiseta (Diptera, Muscidae) - ALMEIDA,J. R. de (2001)
The isothermal deterministic model adherence was studied to evaluate the population dinamic of Synthesiomyia nudiseta (Diptera, Muscidae). The linear form of equation obtained for the experiments in the several phases, were for Egg: 1/D = -0.18 + 0.02 . T; Larva: 1/D = -0.028 + 0.01. T; Pupa: 1/D = -0.069 + 0.01 . T; and Adult: 1/D = -0.4178 + 0.02 . T. In function of temperature, S. nudiseta can present from 4.18 to 8.95 and from 4.91 to 8.99 generations per year, when calculated through the equations of development and through the simulations, respectively. And the higher the temperature the larger the generation number. Through variance analysis it was verified the significance for the regression equations in relation to the annual generation number (Ng/year) of S. nudiseta in function of the isothermals, for two studied situations. It was obtained a significance of 0,1%. The regression equations obtained for these situations were: Ng/year = 5.4 + 0.5 . T and Ng/year = 5.1 + 0.52 . T. The number of generations of S. nudiseta varies linearly with the isothermal. Besides that, the number of annual generations for each isothermal does not differ statistically when calculated through the development equations or through the simulations. Such conditions suggest the adaptation of the deterministic model adopted.